The Effect of Emotional Intelligence on Mathematics Learning Outcomes of Grade V Students of SD N Pundenarum 3, Demak Regency - Yulinda Putri, Gracelia; Fajriyah, Khusnul; Purnamasari, Veryliana (Indonesian Academy of Social and Religious Research (IASRR), 2024)
Education is an effort to shape students from their nature into a better person and humanize humans. Intelligence Quotient (IQ) and Emotional Intelligence (EI) must be balanced. Learning outcomes are a result of the learning process using measurement tools in the form of tests that are prepared in a planned manner such as written tests, oral tests, and action tests. The learning outcomes of each learner can be different for each individual. Based on the results of observations and interviews with fifth grade teachers of SD N Pundenarum 3 Demak Regency, it is known that the learning outcomes of students are still lacking, especially in Mathematics subjects. There are still many students who pay less attention to the lesson. This study aims to analyze how emotional intelligence affects the learning outcomes of 5th grade students in mathematics subjects at SD N Pundenarum 3 Demak. The method used is quantitative. Data collection techniques using questionnaires and documentation. Data analysis techniques used are normality test, linearity test and hypothesis testing using SPSS. The results obtained are that there is a significant influence of emotional intelligence on the mathematics learning outcomes of fifth grade students of SDN Pundenarum 3 Demak.